Total internal partition sums for 166 isotopologues of 51 molecules important in planetary atmospheres: Application to HITRAN2016 and beyond. (December 2017) - Gamache, Robert R.; Roller, Christopher; Lopes, Eldon; Gordon, Iouli E.; Rothman, Laurence S.; Polyansky, Oleg L.; Zobov, Nikolai F.; Kyuberis, Aleksandra A.; Tennyson, Jonathan; Yurchenko, Sergei N.; Császár, Attila G.; Furtenbacher, Tibor; et al.
Abstract: Total internal partition sums (TIPS) are reported for 166 isotopologues of 51 molecules important in planetary atmospheres. Molecules 1 to 50 are taken from the HITRAN2016 list, and, in some cases, additional isotopologues are considered for some of the molecules. Molecules 51–53 are C3 H4, CH3, and CS2, respectively. TIPS are not reported for the O atom and CF4 ; thus, while there are 53 species in the list, data are reported for 51 molecules. The TIPS are determined by various methods from 1 K to a T max that ensures the TIPS reported have converged. These data are provided with HITRAN2016 and a new version of the TIPS code is available in both FORTRAN and python languages. Highlights: Total internal partition sums (TIPS) are reported for 166 isotopologues of 51 molecules important in planetary atmospheres. TIPS are reported from 1 K to a T max that insures the TIPS have converged. The new versions of the TIPS code are available in both FORTRAN and python languages.